Neurometabolic abnormalities in schizophrenia and depression observed with magnetic resonance spectroscopy at 7 T. Issue 1 (January 2017) - Taylor, Reggie; Osuch, Elizabeth A.; Schaefer, Betsy; Rajakumar, Nagalingam; Neufeld, Richard W. J.; Théberge, Jean; Williamson, Peter C.
Abstract : Background: Examining neurometabolic abnormalities in critical brain areas in schizophrenia and major depressive disorder (MDD) may help guide future pharmacological interventions including glutamate-modulating treatments. Aims: To measure metabolite concentrations within the anterior cingulate cortex (ACC) and thalamus of people with schizophrenia and people with MDD. Methods: Spectra were acquired from 16 volunteers with schizophrenia, 17 with MDD and 18 healthy controls using magnetic resonance spectroscopy on a 7 Tesla scanner. Results: In the thalamus, there were lower glycine concentrations in the schizophrenia group relative to control ( P =0.017) and MDD groups ( P =0.012), and higher glutamine concentrations relative to healthy controls ( P =0.009). In the thalamus and the ACC, the MDD group had lower myo -inositol concentrations than the control ( P =0.014, P =0.009, respectively) and schizophrenia ( P =0.004, P =0.002, respectively) groups. Conclusion: These results support the glutamatergic theory of schizophrenia and indicate a potential glycine deficiency in the thalamus. In addition, reduced myo -inositol concentrations in MDD suggest its involvement in the disorder.